Higher education systems 3.0 : harnessing systemness, delivering performance - Lane, Jason E.; Johnstone, D. Bruce (Donald Bruce), 1941- (Albany : State University of New York Press, 2013)
"A comprehensive examination of higher education multi-campus systems and their role in improving state economies and communities"--Provided by publisher.
part I. The history and definition of systemness -- part II. Challenges to system innovation : unpacking the tensions -- part III. Emerging roles for systems.
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Palo Alto, Calif. : ebrary, 2013. Available via World Wide Web. Access may be limited to ebrary affiliated libraries.
Keywords: Higher education and state -- United States -- States; Education, Higher -- United States -- States; Education, Higher -- United States -- States -- Administration; Education, Higher -- United States -- Finance; Electronic books